Clinical Outcomes of Patients with Advanced Cancer and Pre‐Existing Autoimmune Diseases Treated with Anti‐Programmed Death‐1 Immunotherapy: A Real‐World Transverse Study. (22nd February 2019) - Cortellini, Alessio; Buti, Sebastiano; Santini, Daniele; Perrone, Fabiana; Giusti, Raffaele; Tiseo, Marcello; Bersanelli, Melissa; Michiara, Maria; Grassadonia, Antonino; Brocco, Davide; Tinari, Nicola; De Tursi, Michele; et al.
Abstract: Background: Patients with a history of autoimmune diseases (AIDs) have not usually been included in clinical trials with immune checkpoint inhibitors. Materials and Methods: Consecutive patients with advanced cancer, treated with anti‐programmed death‐1 (PD‐1) agents, were evaluated according to the presence of pre‐existing AIDs. The incidence of immune‐related adverse events (irAEs) and clinical outcomes were compared among subgroups. Results: A total of 751 patients were enrolled; median age was 69 years. Primary tumors were as follows: non‐small cell lung cancer, 492 (65.5%); melanoma, 159 (21.2%); kidney cancer, 94 (12.5%); and others, 6 (0.8%). Male/female ratio was 499/252. Eighty‐five patients (11.3%) had pre‐existing AIDs, further differentiated in clinically active (17.6%) and inactive (82.4%). Among patients with pre‐existing AIDs, incidence of irAEs of any grade was significantly higher when compared with patients without AIDs (65.9% vs. 39.9%). At multivariate analysis, both inactive ( p  = .0005) and active pre‐existing AIDs ( p  = .0162), female sex ( p  = .0004), and Eastern Cooperative Oncology Group Performance Status <2 ( p  = .0030) were significantly related to a higher incidence of irAEs of any grade. No significant differences were observed regarding grade 3/4 irAEs and objective response rate among subgroups. Pre‐existing AIDs were not significantly related with progression‐free survival and overall survival. Conclusion: This study quantifies the increased risk of developing irAEs in patients with pre‐existing AIDs who had to be treated with anti‐PD‐1 immunotherapy. Nevertheless, the incidence of grade 3/4 irAEs is not significantly higher when compared with control population. The finding of a greater incidence of irAEs among female patients ranks among the "hot topics" in gender‐related differences in immuno‐oncology. Abstract : This article reports on treatment of advanced cancer with anti‐PD1 antibodies, focusing on patients with pre‐existing autoimmune disorders.